2019
DOI: 10.30607/kvj.505685
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance To Campylobacter spp. Isolated from The Livers of Slaughtered Ruminants and Aborted Ovine Fetuses

Abstract: The presence of Campylobacter spp. obtained from clinically healthy 50 sheep, goats and cattle slaughtered in slaughterhouses in Afyonkarahisar and Kutahya provinces and 44 aborted ovine fetuses obtained from the same region was investigated in this study. The subtypes were isolated by culture methods and identified by API Campy (Biomerieux, France) test kits. Campylobacter spp. was isolated from 7 samples (15.91%) out of 44 aborted ovine fetuses. After identification of Campylobacter spp., it was determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The resistance of Campylobacter fetus subsp. fetus was also reported by Kenar and Gökçe (2019). The bacteria were isolated from the livers of slaughtered ruminants and aborted ovine fetuses.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The resistance of Campylobacter fetus subsp. fetus was also reported by Kenar and Gökçe (2019). The bacteria were isolated from the livers of slaughtered ruminants and aborted ovine fetuses.…”
Section: Discussionmentioning
confidence: 95%
“…The bacteria were isolated from the livers of slaughtered ruminants and aborted ovine fetuses. Their results, based on the disk diffusion method, revealed that the highest resistance was manifested against ciprofloxacin and tetracycline (45.45%) while the highest sensitivity was against gentamicin (90.91%) and chloramphenicol (100%) (Kenar and Gökçe, 2019). These findings slightly differ from the results of the present study; though both studies used disc diffusion methods, it was observed that the resistance to ciprofloxacin and tetracycline was higher when compared with the previous study, respectively 63.0% and 59.3%.…”
Section: Discussionmentioning
confidence: 99%